2007
DOI: 10.3174/ajnr.a0639
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Spinal MR Angiography: Initial Clinical Experience in the Evaluation of Spinal Arteriovenous Shunts

Abstract: BACKGROUND AND PURPOSE:Spinal arteriovenous shunts usually require digital subtraction angiography (DSA) for evaluation. We report a unique time-resolved spinal MR angiographic (TRSMRA) technique with a temporal resolution of 3-6 seconds and spatial resolution of approximately 1 mm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 14 publications
3
37
0
Order By: Relevance
“…Ali et al 23 described the use of a TR-MRA (TRICKS) sequence to predict the level of SDAVF to within 1 vertebral level in 6 patients. The authors also suggested that the technique was accurate for excluding the presence of SDAVFs and in confirming successful fistula occlusion following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al 23 described the use of a TR-MRA (TRICKS) sequence to predict the level of SDAVF to within 1 vertebral level in 6 patients. The authors also suggested that the technique was accurate for excluding the presence of SDAVFs and in confirming successful fistula occlusion following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, spinal angiography is invasive and associated with several risks 2) . Recanalization or collateral development should be considered and confirmed by spinal angiography in patients whose symptoms recur or become aggravated during the early follow-up period after embolization therapy.…”
Section: Follow-up Strategymentioning
confidence: 99%
“…Other published reports demonstrating high sensitivity and reasonably high specificity of dynamic Gd-enhanced MRA for detection of spinal DAVFs support this assertion. 3,10,26 Clinical history and the suspicion of a spinal DAVF should ultimately remain the deciding factors that determine whether one should proceed with spinal angiography. However, in cases involving patients who do not present with diagnostic MRI findings or typical symptoms of a spinal DAVF, MRA examination may provide compelling evidence to go on to invasive conventional angiography.…”
Section: Discussionmentioning
confidence: 99%